KAFALAH BI AN NAFS DAN JAMINAN ORANG DALAM PENANGGUHAN PENAHANAN - Hanif Azhar; Patsun (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2021)
This research is based on the editorial of article 31 paragraphs 1 and 2 of the Criminal Procedure Code (KUHAP) regarding the possibility of a suspension of detention for a suspect or defendant on bail. The phrase